Neural correlates of risk perception: HIV vs. leukemia - Barth, Alexander; Schmaelzle, Ralf; Renner, Britta; Schupp, Harald T. (Frontiers in Behavioral Neuroscience, 2013)
Field studies on HIV risk perception suggest that people may rely on impressions they have about the safety of their partner. Previous studies show that individuals perceived as 'risky' regarding HIV elicit a differential brain response in both earlier (~200 - 350 ms) and later (~350 - 700 ms) time windows compared to those perceived as safe. This raises the question whether this ERP response is specific to contagious life-threatening diseases or a general mechanism triggered by life-threatening but non-contagious diseases. In the present study, we recorded dense sensor EEG while participants (N = 36) evaluated photographs of unacquainted individuals for either HIV or leukemia risk. The ERP results replicated previous findings revealing earlier and later differential brain responses towards individuals perceived as high risk for HIV. However, there were no significant ERP differences for high vs. low leukemia risk. Rather than reflecting a generic response to disease, the present findings suggest that intuitive judgments of HIV risk are at least in part specific to sexually transmitted diseases.